Business sustainability challenges in the face of technology and digital literacy: a study of Micro, Small, and Medium Enterprises - Indra Permana; Bagus Hari Sugiharto; Soni Suardi; Eri Mardiani; Iwan Riswandi (International Journal on Social Science, Economics and Art, 2024)
The study investigates Micro, Small, and Medium Enterprises (MSMEs) within the Tanjung Lesung tourism sector in Banten Province. It focuses on the application of digital literacy for business sustainability in the contemporary technological landscape. The research employed a qualitative descriptive research method involving observation and in-depth interviews. Data was collected through observation and in-depth interviews. Analysis involved data reduction, display, and conclusions drafting. The findings underscore the pivotal role of digital technology in fostering business continuity. The study emphasizes MSMEs' pursuit of sustainability through tailored strategies, including the attainment of sustainability certifications to bolster market presence, particularly in eco-conscious segments.